2011
DOI: 10.1007/s00464-011-1873-0
|View full text |Cite
|
Sign up to set email alerts
|

Selective tissue elevation by pressure for endoscopic mucosal resection of colorectal adenoma: first clinical trial

Abstract: This first clinical trial to analyze STEP technique demonstrated that STEP used to elevate large mucosal lesions in any location is feasible and facilitates EMR for colorectal adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…3c ). Bleeding rate was particularly high in the study by Belle et al 25 , in which 25/66 patients required hemostasis with clips. If this atypical study is excluded, the bleeding rate is 4.8 % (95 % CI 3.4 %-6.5 %) and remains significantly higher with EMR.…”
Section: Resultsmentioning
confidence: 90%
“…3c ). Bleeding rate was particularly high in the study by Belle et al 25 , in which 25/66 patients required hemostasis with clips. If this atypical study is excluded, the bleeding rate is 4.8 % (95 % CI 3.4 %-6.5 %) and remains significantly higher with EMR.…”
Section: Resultsmentioning
confidence: 90%
“…We showed that a water jet dissector placed directly on the mucosa resulted in selective deposition of liquid in the submucosa followed by mucosal elevation (lift-off). After animal studies and comparison of different injecting solutions [ 22 , 31 ], we presented the first data from clinical application [ 32 ]. A total of 59 patients underwent resection of 70 lesions with a maximum diameter of 80 mm (mean 27 mm).…”
Section: Application Methodsmentioning
confidence: 99%
“…dual, hook, insulation-tipped (IT), triangle-tipped (TT) [ 18 , 19 , 20 , 21 ]), some of them allowing also for submucosal injection (e.g. flush knife [ 22 ] or hybrid knife [ 23 , 24 ]). Hemostasis during the dissection procedure is achieved either with the knife itself in coagulation mode or – in the case of larger vessels – with dedicated hemostatic forceps or hemoclips.…”
Section: Practical Aspects Of Colorectal Esdmentioning
confidence: 99%
“…These substances allowed long-lasting elevation and more efficient dissection [ 72 , 73 , 74 ] and even had autodissective properties [ 75 ], thus greatly reducing procedure time. Moreover, the hybrid knife [ 23 , 24 ] or flush knife [ 22 ] allow submucosal injection and dissection to be carried out with a single device. Finally, specific cutting devices are being evaluated, e.g.…”
Section: Optimizing the Esd Procedure: Current Developmentsmentioning
confidence: 99%